(untitled) (Revista de Biología Marina y Oceanografía, 2024)
A new species of Lepadomorpha barnacles (stalked or pedunculated forms) is described to Chilean deep waters. The specimen was collected in front of Iquique in Tarapacá Region of north Chile, associated to Patagonian Toothfish Dissostichus eleginoides fishery about 1000 m deep, and belong to a new species wish is the first record of the family Poecilasmatidae to Southeast Pacific. The genus Glyptelasma is composed by 12 species. G. chilensis is different from all known species because of the reduced peduncle in relation to the capitulum. It has a widening at the base and a minute tooth in the carinal plate. G. chilensis n. sp. is closely related to G. carinatum but differs from it in having only two filamentous appendages on the prosome. G. chilensis n. sp. has a basis of carina with extremes divergent and the wide is widest than the capitulum. The combinations of morphological characters allow the description of a new species for the genus Glyptelasma. With this first record to East Pacific of Glyptelasma, it could be inferred that the genus has a Tethyan distribution.